Towards generic rule-based visual programming - Hoffmann, Berthold; Minas, Mark (Proc. IEEE Symposium on Visual Languages 2000, 2000)
DIAPLAN is visual, rule-based programming language and a generic environment for implementing visual languages. It offers object-oriented programming for graph transformation and support graph typing and structuring. It also provides information for domain-specific diagram representation of graph in visual languages and users interaction with these diagrams.
UnivIS-Import:2015-04-16:Pub.2000.tech.IMMD.IMMD2.toward_2